Pengetahuan dan Sikap Ibu Hamil Trimester Tiga Tentang Edukasi ASI Eksklusif - Samosir , Hernawati Romauli; Saputri , Fatmawaty; Buulolo , Eunike Stefhani; Simangunsong , Eva Zhurnita; Sitanggang, Ester Aprilda; Paninsari, Debora (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2025)
Background: According to data from the World Health Organization (WHO), only 38% of infants aged 0–6 months worldwide were exclusively breastfed, with an increase to 44% in 2020. The low coverage of exclusive breastfeeding is influenced by mothers’ lack of knowledge and attitudes regarding its importance. Objective: This study aims to examine the effect of education on the knowledge and attitudes of third-trimester pregnant women regarding exclusive breastfeeding. Methods: A quantitative approach was employed using a one-group pretest and posttest design within a cross-sectional framework. The sample consisted of 35 third-trimester pregnant women selected through total sampling at BPM Juliana Dalimunthe, S.Keb., Bdn, located in Tembung, Deli Serdang Regency, in November 2024. Data were collected using questionnaires and analyzed using the paired sample t-test. Results: There was a significant improvement in the knowledge and attitudes of pregnant women after receiving the educational intervention. The mean knowledge score increased from 70.86 to 76.00, and the attitude score from 72.11 to 79.71, with a p-value of 0.00 (< 0.05) for both variables. Conclusion: Education on exclusive breastfeeding has a significant effect on improving the knowledge and attitudes of third-trimester pregnant women. These findings highlight the importance of health education in preparing mothers for successful exclusive breastfeeding.